PENGELOLAAN SURAT MENYURAT DALAM ADMINISTRASI PERKANTORAN - Kasim, Siti Fatimah Ibrahim; Alpiah, Mega Rahmania; Amir, Nurafiat (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
Correspondence management is an essential component of office administration as it serves as an official communication medium and a means of managing organizational information. A systematic correspondence management system contributes to administrative order, facilitates the flow of information, and enhances the effectiveness of organizational operations. This study aims to examine the concept of correspondence management in office administration through a literature review, covering the concepts of correspondence, office administration, incoming and outgoing mail management, document filing and archiving systems, the utilization of digital technology, challenges in correspondence management, and strategies for improving its effectiveness. This study employed a qualitative literature review approach by collecting data from books, scientific journals, and other relevant academic sources. The collected data were analyzed using content analysis to identify, compare, and synthesize concepts and findings from previous studies. The results indicate that systematic correspondence management supported by digital technology improves the effectiveness of office administration by accelerating information flow, enhancing document organization, and increasing work efficiency. However, its implementation continues to face several challenges, including limited human resource competencies, inadequate infrastructure, and inconsistencies in administrative procedures. Therefore, strengthening administrative systems, improving human resource capabilities, and optimizing the use of digital technology are necessary to establish an effective, efficient, and accountable correspondence management system.